Satisfaction of Primary Healthcare Dentists after the Completion of a Distance Learning Course in Pediatric Dentistry - Caren Serra BAVARESCO; Silvana BRAGANÇA; Francine de Paula FRIES; Giordano Santana SÓRIA; Flávio Renato Reis DE MOURA; Elken Gomes RIVALDO; Otávio Pereira D´ÁVILA; Roberto Nunes UMPIERRE; Erno HARZHEIM; Jonas Almeida RODRIGUES (Tehran University of Medical Sciences, 2019)
Background: The aim of the present study was to assess the level of satisfaction of dentists working in primary healthcare (PHC) with a Distance learning (DL) course in pediatric dentistry offered by the TeleHealthRS center, and to the investigate possible associations between the variables indicative of their satisfaction and their performance on the questionnaires applied before and after the course. Methods: The course was offered in 2015 by the Federal University of Rio Grande do Sul (UFRGS) together with the TeleHealthRS center in Brazil. Data were collected on the participants' personal and professional profile, their pre- and post-course knowledge about pediatric dentistry, and their satisfaction with the course. Student's t-test and the ANOVA test were used to assess the possible associations between the variables indicative of their satisfaction and their performance on the questionnaires applied before and after the course. Results: Overall, the participants were satisfied with the course, however, no statistically significant association was found between the variables indicative of their satisfaction and the grades they earned on the pre- and post-course questionnaires. Conclusion: The available pediatric dentistry course received positive evaluations from the participants, constituting a possible strategy for the qualification of primary care dentists. Future studies are warranted to further investigate the expectations of DL course participants, aiming to enhance the quality of future editions of this learning modality for pediatric dentistry contents.